Incidence and epidemiological features of acute pancreatitis among adult inhabitants in Qatar - Abdel-Naser Elzouki; Omar Alsaed; Abazar Saeed; Ahmed Ayash; Fahmi Yousef Khan (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Acute pancreatitis (AP) is one of the most common gastrointestinal causes of hospital admission in Qatar. The aim of the present study was to investigate the epidemiological features and demographic characteristics of patients with AP and to estimate the annual incidence rates of this disease among adult inhabitants in Qatar. Materials and Methods: This retrospective study was conducted using the data collected by reviewing records of patients with AP admitted to the medical and surgical wards of Hamad GeneralHospital and Alkhor Hospital, Qatar from January 2007 to December 2012. Diagnosis of AP was based on abdominal pain suggestive of AP, serum lipase and/or amylase at least three times the upper limit of normal, and/or characteristic findings of AP on abdominal ultrasound or computed tomography. Results: A total of 382 AP events were reported in 334 patients. There were 250 (75%) males and 84 (25%) females. The mean age (±SD) of the patients was 56.8±18.7 years. Gallstone disease (40.6%) was the highest cause of AP, followed by alcohol consumption (28.5%) and idiopathic AP (20.7%). The mean annual incidence rate of AP was 5 per 100,000 adult inhabitants in Qatar from January 2007 to December 2012. The incidence rate among men was higher than that among women. Mortality rate was low (0.3%), and there were complications in 112 (29.3%) patients. Conclusion: The annual incidence rate of AP is relatively low in Qatar and tends to behave similar to many European countries in etiology, which can be explained by population structure. Gallstone and alcohol consumption are the main causes, and idiopathic AP is responsible for more cases than expected. Cite this article as: Elzouki AN, Alsaed O, Saeed A, Ayash A, Khan FY. Incidence and epidemiological features of acute pancreatitis among adult inhabitants in Qatar. Turk J Gastroenterol 2019; 30: 95-100.